Factors Affecting Forage Quality - Adegbola T. Adesogan; Lynn E. Sollenberger; J. E. Moore; Yoana C. Newman; Joao M. B. Vendramini (EDIS)
Revised! SS-AGR-93, a 5-page illustrated fact sheet by A. T. Adesogan, L. E. Sollenberger, Y. C. Newman, and J. M. B. Vendramini, discusses forage quality and factors affecting intake and nutritive value. Includes additional sources of information. Published by the UF Department of Agronomy, June 2009.